Résolution des équations de Saint Venant par un schéma éléments finis et un schéma volumes finis - Boulerhcha, Mohammed; Boushaba, Farid; Elmahi, Imad; Amaoui, Hamid (European Journal of Computational Mechanics, 2005)
Two dimentionnal shallow water equations are resolved by two different methods. The first one, is centred and is the finite element type. The second one, is an upwind method and is finite volume type. Both methods are second order in space and time. The validity of the two methods is demonstrated over examples and their performances are analysed and compared.